Perancangan Sistem Pengukuran Kinerja Pada Rumah Sakit dengan Menggunakan Metode Balanced Scorecard - Ahmad Mubin (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
Elizabeth Hospital of Situbondo represent one of the some hospital exist in Sub-province of Situbondo. With condition of like this is existing hospital have to show maximal performance and can give best service to society so that can become hospital society choice. Beside give service of health, as a hospital unit also have compulsion to always ever take care of the continuity of its life, even the including all existing shares or unit to expand in an optimal fashion. With condition of above, hence company in this case RS. Elizabeth Situbondo can become company of which can exploit system measurement of performance by using method of balanced scorecard to increase company performance on an ongoing basis so that can give required service consumer swiftly is, effective, inwrought, and professional. At this research of concept which is used in designing system measurement of performance balanced scorecard. As for in perspective which used in this research cover five in perpective that is finance, cutomer or client, internal business process, study and growth, and benefit to society. From this in perpective fifth is later then developed to become performance indicators able to be measured to utilize to know level attainment of Hospital performance. Pursuant to determination of performance indicator is later then conducted measurement by using ill obtained datas from home every its indicator, this measurement use objective matrix (OMAX), where hospital periodical can do planning and control to attainment of performance. In measurement use OMAX, included also wight element of each measured indicator, where in determination of wight every the indicator use analytical hierarchy process ( AHP). In measurement of in perpective fifth conducted performance yield 23 indicator. Result of performance measurement in 2007, index attainment of performance equal to 6,616.